Faktor-Faktor Yang Mempengaruhi Peran Audit Internal Dalam Pencegahan Fraud: Independensi Dan Objektivitas Auditor, Sistem Pengendalian Internal Yang Kuat Dan Sumber Daya Yang Memadai Dan Kompeten - Fiki Nofembri; Cris Kuntadi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
This study aims to examine the factors that influence the role of internal audit in fraud prevention within organizations. The role of internal audit is crucial in detecting and preventing fraud, so its effectiveness needs to be supported by several key factors. This article reviews the factors that affect the role of internal audit in fraud prevention, including Auditor Independence and Objectivity, Strong Internal Control Systems, and Adequate and Competent Resources, which are all aspects of human resource management studies. The purpose of writing this article is to develop hypotheses regarding the relationships between these variables for use in future research. The findings from this literature review are: 1) Auditor Independence and Objectivity have an effect on the role of internal audit in fraud prevention;2) Strong Internal Control Systems affect the role of internal audit in fraud prevention; and 3) Adequate and Competent Resources influence the role of internal audit in fraud prevention.